On the Asymptotic Behavior of a Subcritical Branching Process with Immigration - Khusanbaev, Ya. M. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We study a subcritical branching process with inhomogeneous immigration in the case where the mean value and variance of immigration are regularly varying at infinity. We show that a properly normalized subcritical process with immigration weakly approaches a deterministic process and prove the limit theorem for the fluctuation of this process.